Prevelance of Emeria Genera Upon Coccidiosis Infection Toward Male Layer - Emantis Rosa; Nadia Eka Yulian; Purnama Edy Santosa (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Chicken is one of the bird species used as a source of animal protein which is very enjoyable and known by society. One chicken species that widely cultivated are the male layer. However, there was frequently obstacle in the maintenance, one is caused by parasite species of coccidia that causes coccidiosis. This research is conducted in November 2016 on a livestock farm, Kelurahan Segalamider, Kecamatan Tanjung Karang Barat, Kota Bandar Lampung. This research aims to determine the type of parasite egg that causes coccidiosis and to determine the prevalence of coccidia attack on the male layer. This research uses a proportionate clustered random sampling method, which took 100 samples of the male layer faces randomly from each cage as much as 25 samples. The identification using the guide book of Conway and McKenzie (2007) and the calculation of the number of parasite eggs using EPG Mc. Master assay in Balai Veteriner Lampung. Data were analyzed descriptively by displaying data in tables and figures. The result showed that there are five species of Eimeria, namely Eimeria tenella, Eimeria maxima, Eimeria brunetti, Eimeria nikamae, and Eimeria mitis that found in oocyst sporulated form and oocyst not sporulated. The parasite causes coccidiosis in the male layer is Eimeria tenella with prevalence values of coccidia attack by 20%.